Evaluation Efficacy of Clarithromycin and Levofloxacin in the Eradication of Helicobacter Pylori (H.P) Infected Iraqi Patients at Al-Yarmouk Teaching Hospital - Marwan Majeed Ibrahim1, Mohamed Ghalib Zakari2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Helicobacter pylori (H.P) infection is an increasing concern in modern medicine due to its effect on the pathogenesis and management of peptic ulcer disease and gastritis and its possible link to gastric adeno carcinoma cases. The eradication of HP is a mandatory approach in documented cases of HP infection mainly gastric and duodenal ulcers. The treatment options is variable globally according to microbial susceptibility test and local guidelines. This study focused on two main options in the eradication of HP and found that levofloxacin based therapy is superior to clarithromycin based approach in the rate of eradication , with comparable rate of adverse events.